Analysis of health insurance policy effectiveness and household health expenditure on healthcare equity - Romliyadi Romliyadi (JAKESPOL Journal of Health Policy Analysis, 2026)
Introduction: Healthcare inequity remains a major challenge despite the expansion of national health insurance programs in developing countries. This study aimed to analyze the effectiveness of health insurance policies and examine the influence of household healthcare expenditure on healthcare equity. Methods: A quantitative cross-sectional analytical study was conducted in South Sumatra, Indonesia, between January and April 2026. A total of 84 respondents were selected using multistage cluster sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics, chi-square tests, and multivariate logistic regression with a significance level of α = 0.05. Results: Low health insurance policy effectiveness significantly increased the likelihood of poor healthcare equity (AOR = 3.56; 95% CI: 1.34–9.47; p = 0.011). High household healthcare expenditure was also associated with inequitable healthcare access (AOR = 3.24; 95% CI: 1.20–8.73; p = 0.019). Rural residence and low household income independently contributed to healthcare disparities. Conclusion: Healthcare equity is strongly influenced by policy implementation quality and household financial burden. Strengthening financial protection, improving healthcare accessibility, and enhancing health system responsiveness are essential to reduce healthcare inequities.